[Highway strip maps of Australia]. Kulgera-Ayers Rock-Kulgera, 317.6 km., (via Stuart Highway, Mt. Ebenezer H.S. & Curtin H.S.) - Royal Automobile Association; Royal Automobile Association of South Australia ([Adelaide] : RAA, 1981)
Highway strip map describing places, country traversed, points of interest, road conditions and safety hints for motorists.
On verso: Diagrams of Ayers Rock (Uluru) and the Olgas (Katajuta).
Keywords: Ayers Rock Region (N.T.) -- Maps